Role of Probiotics in Reducing the Frequency of Necrotizing Enterocolitis in Adults - Zahoor Ahmed Shah, Syedda Alia Hassan Bukhari, Jalal Khan, Tuba Rasheed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the role of probiotics in reducing the frequency of necrotizing enterocolitis in adults. Study design: Retrospective study Place and duration of study: Department of Medicine, Bolan Medical College Quetta from 1st July 2021 to 31st December 2021. Methodology: Forty cases of adult necrotizing enterocolitis were examined clinically as well as through radiological, biochemical and microbiological testing were enrolled. The cases were categorized according to the severity of their disease and probiotics were used for a month in less severe cases for analyzing its role in reducing necrotizing enterocolitis with a one-month follow-up. Results: The mean age of the patients was 49.2±5.36 years with 27 cases of males in comparison to 13 cases of females. Metabolic acidosis and respiratory acidosis were presented only in stage 2 and 3 each respectivelyAround 43% of cases reported reduction in venous ammonia after probiotic usage while 21% of the patients claimed betterment in their cognition. Conclusion: Probiotics have an efficient role in reducing ammonia production and improving cognition in adult necrotizing enterocolitis.